An investigation of the psychometric properties of the Structured Objective Rorschach Test (SORT) used as a measurement of personality for a group of college students - Gunston, Pamela Elaine (Stellenbosch : Stellenbosch University, 2012)
Assignment (M.A.) -- University of Stellenbosch, 1987.